Design of a Simple Wastewater Treatment Plant at Darul Falah Islamic Boarding School, Banyuwangi - Imam Thohari; Dewi Anggita; Pratiwi Hermiyanti; Cecep Dani Sucipto (Poltekkes Kemenkes Surabaya, 2024)
Domestic wastewater discharged directly into rivers can affect the environment that will accommodate the water. The more waste water produced, the greater the capacity used to accommodate the wastewater. This study aims to plan the design of the wastewater Treatment Plant (WWTP) and the WWTP treatment system in accordance with the domestic waste generated by the male dormitory of the Darul Farah Islamic Boarding School. This research method is using descriptive research type. Data were collected through field observations, namely by observing and measuring the discharge and domestic wastewater disposal system in the male dormitory of the Darul Falah Islamic Boarding School, then the collected data were analyzed descriptively. Based on the results of the research, the clean water debit used for activities in the male dormitory of the Darul Falah Islamic Boarding School is 22.2 m3/day, so that the resulting wastewater discharge is 17.76 m3/day. The planned WWTP design uses the Anaerobic Baffled Reactor (ABR) method with a width of 2.6 m, a length of 9.6 m, and a height of 2 m. The WWTP design used for the male dormitory of the Darul Falah Islamic Boarding School is the Anaerobic Baffled Reactor (ABR). It is recommended for Islamic boarding schools to realize the construction of WWTPs for wastewater treatment in male dormitories so as not to pollute the environment.